Late-stage ligand functionalization via the Staudinger reaction using phosphine-appended 2, 2′-bipyridine. Issue 46 (13th May 2021) - Taher, Deeb; Wilson, Jessica R.; Ritch, Grayson; Zeller, Matthias; Szymczak, Nathaniel K.
Abstract : Phosphine-appended-2, 2′-bipyridine serves as a platform for late-stage ligand modifications to install a series of functionalized arenes, including those containing Brønsted and Lewis acidic groups. Abstract : The ability of a phosphine-appended-2, 2′-bipyridine ligand ((Ph2 P)2 bpy) to serve as a platform for late-stage ligand modifications was evaluated using tetrahedral (Ph2 P)2 bpyFeCl2 . We employed a post-metalation Staudinger reaction to install a series of functionalized arenes, including those containing Brønsted and Lewis acidic groups. This reaction sequence represents a versatile strategy to both tune the ligand donor properties as well as directly incorporate appended functionality.